Aligning gender and social inclusion mainstreaming guidelines of Ethiopia with ASARECA’s regional gender policy in East and Central Africa - Barungi, J.; Odeke, M.; Ires, Idil (International Water Management Institute (IWMI), 2024)
IWMI on behalf of the CGIAR initiative “Diversification in East and Southern Africa (Ukama Ustawi)” in partnership with the Ethiopian Ministry of Agriculture (MoA) organized a half-day Gender Mainstreaming Guidelines pre-launch workshop on 10 July 2024 at International Livestock Research Institute (ILRI) Campus, Addis Ababa, Ethiopia. The workshop's objective was to validate and launch the Gender Mainstreaming Guidelines for the MoA. The workshop also sought to discuss partnerships for implementation of the Guidelines. It was attended by 45 participants comprising 14 males and 31 females, representing various key agriculture stakeholders. The workshop was facilitated through PowerPoint presentations and plenary discussions.